Mapping the Application of Language Learning Strategies to the Language Skills: A Content Analysis Based on Oxford's Book - Hidayat, Ahmad Fadhel Syakir; Bahruddin, Uril; Mustofa, Syaiful; Duraković, Esad; Abidin, Nadiah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This study aims to map the application of language learning strategies based on Rebecca L. Oxford's theory in her book Language Learning Strategies: What Every Teacher Should Know for four primary skills: listening, speaking, reading, and writing. Using a qualitative approach with content analysis, this study analyzed direct (memory, cognitive, compensatory) and indirect (metacognitive, affective, social) strategies. Data were collected through a literature review and analyzed using the content analysis method based on Klaus Krippendorff's framework. The results showed that memory strategies significantly affected listening and reading skills, cognitive strategies were applied evenly across all skills, while compensatory strategies focused more on speaking skills. Metacognitive and affective strategies are important for learning management, and social strategies support all language skills. The findings guide educators in designing effective teaching methods, particularly in Arabic language learning.